New ecological insights on wild pollinator Andrena hesperia - Emanuele Luigi Zenga; Giovanni Cilia; Marco d'Agostino; Laura Zavatta; Rosa Ranalli; Laura Bortolotti; Simone Flaminio (Journal of Pollination Ecology)
A nesting aggregation of Andrena hesperia in Bologna (Italy) was studied to characterize this bee’s ecology, phenology and interactions with the environment. Andrena hesperia adults emerged between the end of March and the middle of April, displaying univoltine, protandrous phenology. The average resistance to heat stupor of A. hesperia females was 42.53 ± 13.77 minutes at 40°C. Parasites Nomada facilis and Bombylius canescens were associated with the nests. DNA barcode sequences (COI gene) of A. hesperia and N. facilis were sequenced and deposited in GenBank. The gut microbiota of newly emerged individuals was dominated by Bacillota (Lactobacillus and Fructobacillus) and Pseudomonadota (Snodgrassella alvei and Gilliamella). The pollen carried by A. hesperia females was identified morphologically as belonging for the most part to the Asteraceae family. The pathogens detected on A. hesperia showed different infection loads in newly-emerged individuals and foraging adults. This is the first time that comprehensive information on A. hesperia is reported, and it will hopefully foster further studies on this wild bee.